A systematic review on endometriosis during pregnancy: diagnosis, misdiagnosis, complications and outcomes. (7th October 2015) - Leone Roberti Maggiore, Umberto; Ferrero, Simone; Mangili, Giorgia; Bergamini, Alice; Inversetti, Annalisa; Giorgione, Veronica; Viganò, Paola; Candiani, Massimo
Abstract: BACKGROUND: Traditionally, pregnancy was considered to have a positive effect on endometriosis and its painful symptoms due not only to blockage of ovulation preventing bleeding of endometriotic tissue but also to different metabolic, hormonal, immune and angiogenesis changes related to pregnancy. However, a growing literature is emerging on the role of endometriosis in affecting the development of pregnancy and its outcomes and also on the impact of pregnancy on endometriosis. The present article aims to underline the difficulty in diagnosing endometriotic lesions during pregnancy and discuss the options for the treatment of decidualized endometriosis in relation to imaging and symptomatology; to describe all the possible acute complications of pregnancy caused by pre-existing endometriosis and evaluate potential treatments of these complications; to assess whether endometriosis affects pregnancy outcome and hypothesize mechanisms to explain the underlying relationships. METHODS: This systematic review is based on material searched and obtained via Pubmed and Medline between January 1950 and March 2015. Peer-reviewed, English-language journal articles examining the impact of endometriosis on pregnancy and vice versa were included in this article. RESULTS: Changes of the endometriotic lesions may occur during pregnancy caused by the modifications of the hormonal milieu, posing a clinical dilemma due to their atypical appearance. The management of these events is actually challenging as only few cases have been described and the review of available literature evidenced a lack of formal estimates of their incidence. Acute complications of endometriosis during pregnancy, such as spontaneous hemoperitoneum, bowel and ovarian complications, represent rare but life-threatening conditions that require, in most of the cases, surgical operations to be managed. Due to the unpredictability of these complications, no specific recommendation for additional interventions to the routinely monitoring of pregnancy of women with known history of endometriosis is advisable. Even if the results of the published studies are controversial, some evidence is suggestive of an association of endometriosis with spontaneous miscarriage, preterm birth and small for gestational age babies. A correlation of endometriosis with placenta previa (odds ratio from 1.67 to 15.1 according to various studies) has been demonstrated, possibly linked to the abnormal frequency and amplitude of uterine contractions observed in women affected. Finally, there is no evidence that prophylactic surgery would prevent the negative impact of endometriosis itself on pregnancy outcome. CONCLUSIONS: Complications of endometriosis during pregnancy are rare and there is no evidence that the disease has a major detrimental effect on pregnancy outcome. Therefore, pregnant women with endometriosis can be reassured on the course of their pregnancies although the physicians should be aware of the potential increased risk of placenta previa. Current evidence does not support any modification of conventional monitoring of pregnancy in patients with endometriosis.